A survey of GFRP composite leaf spring - Rajesh, S.; Nakkeran, S.; Bhaskar, GB. (International Journal of Engineering and Technology, 2014)
Although leaf springs are one of the oldest suspension components, they are still frequently used in the automobile vehicles. Weight reduction is the main focus in the automobile industries. Weight reduction can be achieved primarily by the introduction of better materials, design optimization, and better manufacturing processes. The achievement of weight reduction with adequate improvement of mechanical properties has made composite a very good replacement material for conventional steel. Selection of material is based on the cost and strength of material. The composite materials have more elastic strain energy, storage capacity and high strength to weight ratio compared to steel. This paper briefs about the research carried out for the part of three decades on design, analysis, and selection of material, experiments and fabrication of composite leaf spring.   Keywords: Composite Leaf Spring, Composite Materials, Finite Element Analysis, Weight Reduction, Glass Fiber Reinforced Plastic (GFRP).